2006
DOI: 10.1007/s10551-006-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Multiplicity: Toward an Understanding of the Interactions between Stakeholders

Abstract: While stakeholder theory has traditionally considered organization’s interactions with stakeholders in terms of independent, dyadic relationships, recent scholarship has pointed to the fact that organizations exist within a complex network of intertwining relationships [e.g., Rowley, T. J.: 1997, The Academy of Management Review 22(4), 887–910]. However, further theoretical and empirical development of the interactions between stakeholders has been lacking. In this paper, we develop a framework for understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(240 citation statements)
references
References 41 publications
8
226
1
5
Order By: Relevance
“…Secondly, in using measures of actual power and urgency, we did not take into account any biases that stem from the fact that managerial actions are a result of their perceptions of these actual attributes. Third, (prior) interactions of a company with other stakeholders and between stakeholder groups may influence the priority that managers give to one particular stakeholder (Neville and Menguc 2006;Reid and Toffel 2009;Rowley 1997); therefore disclosure may reflect the combined attributes of several different stakeholder groups. Given our research design, it was not possible to specifically address any potential interdependencies between stakeholders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, in using measures of actual power and urgency, we did not take into account any biases that stem from the fact that managerial actions are a result of their perceptions of these actual attributes. Third, (prior) interactions of a company with other stakeholders and between stakeholder groups may influence the priority that managers give to one particular stakeholder (Neville and Menguc 2006;Reid and Toffel 2009;Rowley 1997); therefore disclosure may reflect the combined attributes of several different stakeholder groups. Given our research design, it was not possible to specifically address any potential interdependencies between stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have refined stakeholder salience theory by means of theoretical contributions, stressing the importance of 'stakeholder proximity' (Driscoll and Starik 2004), interactions between stakeholders (Neville and Menguc 2006) and stakeholder attributes (Neville et al 2011), family firm contexts (Mitchell et al 2011), corporate culture (Jones et al 2007), and other stakeholders' perceptions of salience (Tashman and Raelin 2013). More recent empirical research has suggested more stakeholder characteristics, such as trust and learning potential (Myllykangas et al 2010).…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Stakeholders actively strove to increase their salience, notably by utilising their relationships with others. Neville and Menguc (2006) conclude that stakeholders' potential to influence other stakeholders is frequently determined by the particular nature of their interest, and that they cooperate to increase the persuasive power of their combined interests. This was evident in this case, too, as, for instance, the Argentine government co-operated with CEAG in order to gain more power for its claim within the episode.…”
Section: Discussionmentioning
confidence: 98%
“…Neville and Menguc, 2006), and further proposes that these relationships evolve constantly as interests change between different events. Stakeholders participate actively in the episodes related to their interests.…”
Section: Discussionmentioning
confidence: 99%
“…The interests and expectations of different stakeholders can conflict with one another (Neville and Menguc 2006). As the business environment is not munificent (Staw and Szwajkowski 1975), organizations have to compete for resources in the labor market (for employees), financial market (for capital), supply market (for materials), and customer market (for sales).…”
Section: Pressures and Temptationsmentioning
confidence: 99%